2005
DOI: 10.1021/jf050709v
|View full text |Cite
|
Sign up to set email alerts
|

Solid- and Vapor-Phase Antimicrobial Activities of Six Essential Oils:  Susceptibility of Selected Foodborne Bacterial and Fungal Strains

Abstract: The antimicrobial activity of essential oils (EOs) of cinnamon (Cinnamon zeylanicum), clove (Syzygium aromaticum), basil (Ocimum basillicum), rosemary (Rosmarinus officinalis), dill (Anethum graveolens), and ginger (Zingiber officinalis) was evaluated over a range of concentrations in two types of contact tests (solid and vapor diffusion). The EOs were tested against an array of four Gram-positive bacteria (Staphylococcus aureus, Bacillus cereus, Enterococcus faecalis, and Listeria monocytogenes), four Gram-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
315
4
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 539 publications
(371 citation statements)
references
References 28 publications
27
315
4
10
Order By: Relevance
“…Both essential oils showed a significant antibacterial activity against Gram positive as well as Gram negative bacteria that confirms previous findings [17,41,46]. Thyme essential oil exhibited a higher anti-microbial activity than that of rosemary essential oil, which was similar to the results of the sensitivity test ( Table 2).…”
Section: Antimicrobial Activitysupporting
confidence: 90%
“…Both essential oils showed a significant antibacterial activity against Gram positive as well as Gram negative bacteria that confirms previous findings [17,41,46]. Thyme essential oil exhibited a higher anti-microbial activity than that of rosemary essential oil, which was similar to the results of the sensitivity test ( Table 2).…”
Section: Antimicrobial Activitysupporting
confidence: 90%
“…Wie et al (1997) reported that eugenol reversed neuronal excitotoxic or oxidative injury and had protective effect against N-methyl-D-aspartate-induced neurotoxicity. [22][23][24][25][26][27][28][29]. Eugenol induced cell lysis of Gram-negative and Gram-positive bacteria by damaging the cell wall and membrane caused leakage of protein and lipid contents (Figure 4) [29].…”
Section: Antioxidant Activity Of Eugenolmentioning
confidence: 99%
“…The clove oil has beneficial analgesic, antiseptic, and anesthetic effects [20] and worldwide used in dental medicine. Fungicidal activities of clove oil against yeasts are reported in previous studies [21], and human pathogenic fungi [22]. The study aimed to estimate the fungicidal activity of some disinfectants and plant oils and to know the effect of combination between them at low concentration on growth of Candida albicans.…”
Section: Introductionmentioning
confidence: 99%